Study of the Type Commorbid and Recovery Time Malnourished Under Five Years at the Haliwen Therapeutic Feeding Center, Belu Regency - Benu, Yumi Noviyanti; Jutomo, Lewi; Talahatu, Anna Henny (Lontar : Journal of Community Health, 2023)
Nutritional problems are a threat to the survival of a nation. Malnutrition afflicts toddlers so much that they are called the nutritionally vulnerable group. The goal of this study was to summarize the findings of a study of malnourished children under the age of five at the Therapeutic Feeding Center (TFC) in Belu Regency regarding comorbidities and recovery duration. Descriptive research is the name for this type of study. The children in this study were all under five who had malnutrition and were treated at the Therapeutic Feeding Center in Belu Regency from June 2020 to June 2021. Data analysis techniques were carried out using a computer to calculate the distribution, the average maximum and minimum values. and count presentations. Malnourished children under five with infectious diseases were 87.96%, while without infectious diseases, as much as 12,04%. Types of comorbidities under five with malnutrition are mainly acute respiratory infections 40%, tuberculosis 18,95%, and pneumonia 9,48%. The average recovery time for children under five with malnutrition is 25 days, and the longest is 46 days, and the fastest is four days..